Determinants of pre and post process of corporate merger and acquisition: a study with reference to India - Sharma, Rakesh Kumar (Indian Journal of Economics)
This research paper examines the overall merger and acquisition process and identifies the determinants of successful merger and acquisition for Indian companies. The acquisition process identified for this paper was classified into three stages, i.e, pre-acquisition management, post-acquisition integration, and post-acquisition performance evaluation. This process itself has a crucial role in deciding the success of the acquisition deal. Utilizing information form pervious research, in the present study fifteen dimensions have been identified in three sate of merger and acquisition. These fifteen dimensions were employed as the building blocks of a successful acquisition transition. Through synthesizing multiple an attempt has been made to identify the content of specific factors that has affected a successful merger and acquisition deal. Specifically, the study attempted to systematically discover evidence about the determents of a successful pre-merger and acquisition management process, and the determinants of successful pre-merger and acquisition management process, and the determinants of successful post-acquisition integration, as well as the post- acquisition performance of acquisition deal. In addition, this study tried to identify important merger and acquisition objectives of acquirer or merging company in India. - Reproduced
Keywords: Takeover, Due diligence